The impact of the mean daily air temperature change on electricity consumption. (August 2015) - Jovanović, Saša; Savić, Slobodan; Bojić, Milorad; Djordjević, Zorica; Nikolić, Danijela
Abstract: This paper presents the analysis of the impact of weather conditions on the consumption of electricity in the City of Kragujevac (the Republic of Serbia) during the seven-year period from 2006 to 2012. It points out the mean daily air temperature as the most influential climate (meteorological) parameter, and gives an overview of deviations from the mean values compared to the reference period. Increases and decreases in the power consumption depending on the deviations of the mean daily temperature from the normal (average) values are also indicated. In periods of strong and long-lasting cold spells in the winter months, there is increased power consumption as a result of heating in residential and office buildings. During extremely hot and long summer periods, there is also a tendency of increasing electricity consumption because of home air conditioning. In the transitional seasons, especially when the remote heating system is not active, sudden and relatively long periods of cold weather also have a significant influence on increases in the electricity consumption. A timely and accurate weather forecast can certainly help prevent the electrical power system overload and reduce the risk of possible power system damages. Highlights: The weather impact from 2006 to 2012 on the consumption of electricity in the City of Kragujevac is analysed. The mean daily air temperature is the most influential climate (meteorological) parameter. Change in power consumption depends on the deviations of the mean daily temperature. In periods of strong cold spells in winter, there is increased power consumption because of home heating. During extremely hot summer periods, there is increased electricity consumption because of home air conditioning.